1995
DOI: 10.1097/00000542-199508000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Actions of Intrathecal U50, 488H, Morphine, or [D-Pen sup 2, D-Pen sup 5] Enkephalin or Intravenous U50, 488H on the Visceromotor Response to Colorectal Distension in the Rat

Abstract: The results suggest that spinal mu- and delta- but not kappa-opioid receptors have a significant role in the modulation of visceral nociception induced by colorectal distension. In addition, the results indicate that activation of nonspinal kappa receptors may mediate visceral antinociception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…This inhibition could not be completely antagonized by very high doses of naloxone or by two -opioid receptor-selective antagonists, nor-Binaltorphimine dihydrochloride (nor-BNI) and DIPPA. Furthermore, in experiments where the cloned rat -opioid receptor (KOR 1) was "knockeddown" at peripheral sites using antisense oligodeoxynucleotides, the dose-dependent inhibition of pelvic nerve afferent fiber responses to noxious CRD by -ORAs persisted (Joshi et al 2000). These results suggested that these peripheral, visceral -ORA actions are mediated by a nonopioid mechanism.…”
Section: Introductionmentioning
confidence: 97%
“…This inhibition could not be completely antagonized by very high doses of naloxone or by two -opioid receptor-selective antagonists, nor-Binaltorphimine dihydrochloride (nor-BNI) and DIPPA. Furthermore, in experiments where the cloned rat -opioid receptor (KOR 1) was "knockeddown" at peripheral sites using antisense oligodeoxynucleotides, the dose-dependent inhibition of pelvic nerve afferent fiber responses to noxious CRD by -ORAs persisted (Joshi et al 2000). These results suggested that these peripheral, visceral -ORA actions are mediated by a nonopioid mechanism.…”
Section: Introductionmentioning
confidence: 97%
“…[ 9,10] Clinical efficacy of Intrathecal Clonidine to relieve visceral pain in well-established [11][12] but Clonidine is also associated with few side effects like bradycardia, hypotension and dry mouth. So, 50μg dose of Clonidine was chosen in our study, as higher doses (150ug) are also associated with significant risk of hypotension as reported by Chiari et, al.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that opioids and  2 adrenergic agonist administered spinally are able to relieve visceral pain [13][14][15][16] . Clinical efficacy of intrathecal opioid to relieve visceral pain is well established [17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical efficacy of intrathecal opioid to relieve visceral pain is well established [17][18] . Antinociceptive action of clonidine exist for both somatic and visceral pain 13,15,16 . In the present study, patients were randomly allocated in three groups: B, BF & BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation